Pemilah Organik dengan Sensor Inframerah Terintegerasi Sensor Induktif dan Kapasitif - Bahtiar, Yusuf Ari; Ariyanto, Dedy; Taufik, Muhammad; Handayani, Trie (Faculty of Engineering, Universitas Brawijaya, 2019)
Every corner of the building and room has been available bin. Not all bins have different colors. This condition makes the performance was less precise and less optimal. Often find out, Â still waste not match in the available place. As a result, inappropriate sorting of waste can cause problems that affect the environment. Convenience Â and beauty can no longer be felt. So, it needs an innovation which waste can be disposed based on its type, so that sorting and service Â becomes easier.